A neural biomarker, the error‐related negativity, predicts the first onset of generalized anxiety disorder in a large sample of adolescent females. (17th April 2018) - Meyer, Alexandria; Nelson, Brady; Perlman, Greg; Klein, Daniel N.; Kotov, Roman
Abstract : Objective: An increased neural response to making mistakes has emerged as a potential biomarker of anxiety across development. The error‐related negativity (ERN) is an event‐related potential elicited when people make mistakes on simple laboratory‐based reaction time tasks that has been associated with risk for anxiety. This study examined whether the ERN prospectively predicted the first onset of generalized anxiety disorder (GAD) over 1.5 years in adolescent girls. Methods: The sample included 457 girls between the ages of 13.5 and 15.5 years, with no history of GAD. At baseline, the ERN was measured using a flankers task. Psychiatric history of the adolescent and biological parent was assessed with diagnostic interviews, and the adolescent completed a self‐report questionnaire regarding anxiety symptoms. Approximately 1.5 years later, adolescents completed the same interview. Results: An increased neural response to errors at baseline predicted first‐onset GAD over 1.5 years. The ERN was a significant predictor independent of other prominent risk factors, including baseline anxiety and depression symptoms and parental lifetime psychiatric history. Jointly the ERN and social anxiety symptoms provided the greatest power for predicting first‐onset GAD. Conclusions: This study provides evidence for the utility of the ERN as a biomarker of risk for GAD during a key developmental period.